2022
DOI: 10.3389/fpubh.2022.810488
|View full text |Cite
|
Sign up to set email alerts
|

Consumption-Related Health Education Inequality in COVID-19: A Cross-Sectional Study in China

Abstract: BackgroundThe COVID-19 pandemic influences various aspects of society, especially for people with low socioeconomic status. Health education has been proven to be a critical strategy in preventing a pandemic. However, socioeconomic characteristics may limit health education among low socioeconomic status groups. This study explores consumption-related health education inequality and the factors that contribute to this, which are variable across China during COVID-19.MethodsThe 2020 China COVID-19 Survey is a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Health care providers also have to pull their weight. Examining the available data and evidence on health inequalities represents a valuable starting to point to identify weaknesses and try to fix them [41].…”
Section: An Issue Coming From the Pastmentioning
confidence: 99%
“…Health care providers also have to pull their weight. Examining the available data and evidence on health inequalities represents a valuable starting to point to identify weaknesses and try to fix them [41].…”
Section: An Issue Coming From the Pastmentioning
confidence: 99%
“…As results show, there are certain groups of people who are more vulnerable, and thus affected more by the policy, which has led to an increase in income inequality. Results show that there indeed has been an increased income inequality since the pre-pandemic period, and that the zero-covid policy has had different effects on different regions, with those in rural regions being affected the most, with the lowest recovery speed and highest income inequality [8]. There were also different effects among the regions, showing the effects on different types of workers.…”
Section: Resultsmentioning
confidence: 91%
“…A survey conducted in rural China during the pandemic revealed that the proportion of telemedicine use was low owing to the barriers of a lack of equipment and knowledge regarding telemedicine access and a lack of trust in and demand for telemedicine [ 36 ]. In addition, health literacy is positively correlated to COVID-19 knowledge, and residents in rural areas have lower health literacy but a lower level of health education on COVID-19 than residents in urban areas [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%